2005
DOI: 10.1074/jbc.m412475200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Vitamin B6 Biosynthesis Pathway in the Human Malaria Parasite Plasmodium falciparum

Abstract: Vitamin B6 is an essential cofactor for more than 100 enzymatic reactions. Mammalian cells are unable to synthesize vitamin B6 de novo, whereas bacteria, plants, fungi, and as shown here Plasmodium falciparum possess a functional vitamin B6 synthesis pathway. P. falciparum expresses the proteins Pdx1 and Pdx2, corresponding to the yeast enzymes Snz1-p and Sno1-p, which are essential for the vitamin B6 biosynthesis. An involvement of PfPdx1 and PfPdx2 in the de novo synthesis of vitamin B6 was shown by compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 50 publications
2
66
0
2
Order By: Relevance
“…The isolation of active protein was confirmed by the ability of YaaE to catalyze the hydrolysis of glutamine, an activity that is dependent on YaaD, its partner protein. (24). However, there is typically a large variation in the amount of activity observed in the glutaminase family of proteins, depending on whether the acceptor domain and its substrates are present or not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The isolation of active protein was confirmed by the ability of YaaE to catalyze the hydrolysis of glutamine, an activity that is dependent on YaaD, its partner protein. (24). However, there is typically a large variation in the amount of activity observed in the glutaminase family of proteins, depending on whether the acceptor domain and its substrates are present or not.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 15 N-labeling studies in yeast had indicated that the nitrogen atom of pyridoxine is derived from the amide moiety of glutamine (9,10), whereas in the E. coli pathway it is derived from glutamate (10,21). Indeed, glutaminase activity has since been demonstrated for the PDX2 proteins of B. subtilis, Saccharomyces cerevisiae, and Plasmodium falciparum (22)(23)(24), designated YaaE (PdxT), SNO1, and PDX2, respectively. However, glutaminase activity was only observed in the presence of PDX1, which was shown to co-purify with PDX2, forming a hetero-oligomeric complex as has been observed for other glutamine amidotransferases (22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PDX1 and PDX2 have been predicted to function as a glutamine amidotransferase with PDX2 as the glutaminase domain and PDX1 as the acceptor͞synthase domain. Indeed, glutaminase activity has been demonstrated for PDX2 from a number of organisms (16)(17)(18). More recently, Burns et al (19) and our own independent studies (51) have been able to reconstitute vitamin B6 formation from intermediates of glycolysis and the pentose phosphate pathway by using the PDX1 and PDX2 homologs from the Gram-positive bacterium Bacillus subtilis.…”
mentioning
confidence: 93%
“…The term "vitamin B6" collectively refers to the vitamers pyridoxal, pyridoxine, and pyridoxamine, and their respective phosphate esters. The metabolically active form is pyridoxal 5Ј-phosphate (PLP), 6 an essential co-enzyme in numerous pathways such as amino acid metabolism and the biosynthesis of antibiotic compounds. In contrast to mammals, which have to take up vitamin B6 from their diet, bacteria, fungi, plants, and the protozoan P. falciparum have the ability to synthesize the vitamin de novo.…”
mentioning
confidence: 99%